A Review of the Trade-Offs across Different Cocoa Production Systems in Ghana - Wainaina, P.; Minang, Peter A.; Duguma, L.A.; Muthee, K. (MDPI, 2021)
Cocoa production is one of the leading causes of deforestation in West Africa. Agroforestry cocoa systems are increasingly promoted as a possible solution to deforestation. This study seeks to understand the trade-offs within agroforestry cocoa in full-sun and high-tech plantation cocoa systems in Ghana. It uses secondary data collected from an extensive literature search. The results established various trade-offs between cocoa yields and other provisioning services derived from the agroforestry services. While the cocoa yields in high-tech systems are almost thrice those in agroforestry systems, the total value of all the provisioning services is highest within the shaded systems. The economic value of per hectarage yield is estimated at USD 8140, USD 5320 and USD 5050 for shaded, full-sun and high-tech systems, respectively. Agroforestry systems also have higher ecosystem services compared to full-sun cocoa and high-tech cocoa systems. The high pesticide use in Ghana′s high-tech cocoa systems is also strongly linked to water and soil pollution, as well as adverse effects on human health. The study concludes that different cocoa production systems in Ghana yield different types of ecosystem provision and are associated with externalities such as the effect of pesticides on soils, water and human health, thus there is a need for the careful consideration of the system from policy and practice perspectives.